Gender matters in Forest Landscape Restoration: A framework for design and evaluation - Elias, Marlène; Ihalainen, Markus; Paez Valencia, Ana Maria (2017)
This brief provides a framework and set of recommendations for enhancing gender equality and women’s rights in and through FLR initiatives. It presents key considerations for gender-responsive FLR, drawing on lessons from the wider gender and natural resource management literature, ongoing and past restoration, and relevant initiatives to alter local land uses for global conservation and development goals.